Bro's brew the production of its new logo and a construction of its visual system - Choresca, Clement John
The function and art of branding is a major contributor to the success of a product or service sold by the company that markets it. To some, brands are just an indicator of identification to distinguish them from others, while others view it as more than trademark for the legal protection of the product or service offered. But branding is beyond building customer loyalty. Successful brands have this power to enter the consumer unconscious, weaving their way into the fabric of everyday life (Phillips, 2006). The world is now filled with every imaginable icon and monogram, as well as all forms of logos. The task of the designers is to take the commonplace ? letterforms, images, geometric shapes ? and make them distinctive and meaningful. According to Adams (2004), this is s unique time, however, and we are able to design in ways unimaginable in the past and that the breadth of opportunity and the possibilities for the designer's involvement in multiple media, combined with the strategies of our client's business, make the logo more than just a nice decoration; it becomes a vital component in a company's success. To be able to do this, a company or organization needs an effective visual identity system that communicates well the corporate image and the quality of the products or services being offered. In this production research, I created a visual identity system that fits and/or creates the personality of Bro's Brew ? a young coffee shop here in Davao City. The study has answered the problems regarding the representation of the business by terms of intensive research about its history, value, attributes, and the nature of business itself. My design was also based on the desires of my client, the message, business information, and target audience. The new logo is primarily concerned with creating an established function for identity branding, influenced by the business's VMG. In the creation of the new logo, I considered 7 steps: (1) Defining the problem and understanding the goal; (2) Research; (3) Inspiration; (4) Sketching and mind-mapping; (5) Digital implementation; (6) Client feedback and revisions; and (7) Final revisions. Initial concepts were brought up and designs were made which later resulted to more variations, and finally arriving at the ultimate design ? a cup of coffee on ?God's hand? with a halo above. With the combination of imagery, typography and color, a visual identity system was established. The new logo reflects now what the current values, personality, goals and vision of Bro's Brew. It tells the audience that Bro's is a coffee shop that offers ?heavenly? taste of coffee highlighted by the halo and connecting it with the brand name ?Bro's? referred to from the history of the business as ?God's representation? in the teleserye May Bukas Pa. The logo is also carefully manipulated in such a way that it will last for long, but can be flexible to change
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts